Habitat use, seasonality and demography of an apex predator: Sevengill shark Notorynchus cepedianus in Northern Patagonia - Irigoyen, Alejo Joaquin (2018)
Gaining insight on how species relate to their environment and other members of the trophic community is critical for their management. We investigated habitat use, seasonal patterns of abundance and population structure of the broadnose sevengill shark Notorynchus cepedianus in the marine temperate environment of a Northern Patagonian bay (Argentina). We expected N. cepedianus to exhibit strong seasonality in the bay driven by the seasonal occurrence of important marine mammal prey. However, an alternative or complementary hypothesis arose from the possibility that N. cepedianus uses the area seasonally as mating grounds. To explore these hypotheses, a suite of baited remote underwater video stations and catch per unit effort data indices were used to estimate the seasonal relative abundance of the species inside the bay. Reproductive hormone levels were measured to determine reproductive status and maturity stages of the population. Results indicated that N. cepedianus uses the bay year-round, showing a peak abundance during spring when individuals aggregate, likely for feeding and mating purposes. Male and female total lengths at maturity were 170 and 190 cm, respectively. Contrary to other studies in the Southwest Atlantic, population composition remained similar throughout the seasons, with adults dominating over juveniles, and adult females prevailing in the population at all times. Considering the historical abundance decline recently reported for the species, protection and enforcement within protected areas across the Southwest Atlantic must remain of high priority in government initiatives.